POLICY PENGEMBANGAN PENDIDIKAN TINGGI ISLAM: Kajian Sistem Pendidikan Negara Malaysia - Robiatur Rohmah; Jamaluddin Jamaluddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
In the decade of the 1960 to 1970, many Malaysians studied at several Islamic universities in Indonesia. Thirty years later, itâ€™s condition turned around, many Indonesian people studyÂ in the abroad. Cause, since the decade of the '70s Malaysia disburse education budget is large enough , both taken from the source and the Colombo Plan Commonwealth Countries , Tengku Abdul Rahman Foundation , and the Ministry of Education itself . Government policy is considered quite daring strategy universal free primary education, which is compulsory for primary school or a free education for all citizens of Malaysia. If the free education policy in Indonesia is carried out after 50 years of independence, free education implemented in Malaysia since 1962, when the country was only 5 years old. With this policy of Malaysia disburse scholarship large enough for good people to study at home and abroad. In addition, in the early decades of the 80s Malaysia establish an international Islamic university, the International Islamic University Malaysia (IIUM) and the International Islamic Institute of Islamic Thought and Civilization (ISTAC) . The college is now one icon development of Islamic studies not only in Southeast Asia but also at the world level.